MEMBANGUN BAHASA KOMUNIKATIF UNTUK ANAK USIA DINI - Rina Devianty (Universitas Islam Negeri Sumatera Utara, 2019)
Language is the most effective communication tool in social interaction. When communicating, communicative language skills are certainly needed by anyone, including children and parents. Parents have a very important role to play in improving communicative language mastery for early childhood. By using communicative language, it is expected to have a positive impact on children's language development. So, children are not only passive language users, but also become active language users.